Lignin phenols records of sediment from the Gåsfjärden lake - Bingjie Yang; Karl Ljung; Wenxin Ning; Helena L Filipsson; Anne Birgitte Nielsen (PANGAEA, 2024)
Terrestrial organic matter (OM) plays a key role in coastal organic carbon burial. However, few studies focus on the relationship between land use in the watershed and the transport of terrestrial OM to coasts from a long-term perspective. In this study, we compared terrestrial OM deposition between an inlet of the Baltic Sea and an upstream lake within the same watershed over the last 500 years, using lignin biomarkers in the sediments. In combination with pollen-based quantitative land cover reconstruction, we assessed the impacts of semicentennial-scale changes in land use on terrestrial OM export. The data is the original dataset of the lignin phenols records of the sediment cores from Gåsfjärden.